The Level of Microbial Contamination of Meat to Local Rams Hare (Lepus nigricollis) on Feed Post Cutting for Giving Waste Wine - P. M. W., Adnyana; Sriyani, N. L. P.; Lindawati, S. A (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
This research aims to analyze the effect of wine waste in diets on microbes in male local rabbits meat. This research was carried out in the village of Tejakula, Buleleng Regency, Tejakula for 16 weeks. Rabbits are used in this study are male rabbit with local age 5-6 week as many as 6 tail. This study used a Randomized Design Group (RAK) consisting of 3 treatment and 2 repeats with each treatment namely waste without using wine ration or ration control (P0), rations that uses 5% waste wine (P1) and the ration using a 10% waste wine (P2). diets and water given ad libitum basis. The observed variable is the TPC (Total Plate Count), the Coliform and e. coli. The results showed that the use of waste wine in rations to TPC (P < 0.05) whiles the Coliform and e. coli did not show the presence of influence. Thus it can be concluded that the use of waste rations of wine as much as 5% and 10% showed good results. Keywords: T he level of microbial contamination, the quality of the meat, waste                     of wine